A Path Analysis of the Effect of Neighborhood Built Environment on Public Health of Older Adults: A Hong Kong Study - Shuangzhou Chen; Shuangzhou Chen; Ting Wang; Zhikang Bao; Vivian Lou; Vivian Lou (Frontiers Media S.A., 2022)
IntroductionHealth deterioration among frail older adults is a public health concern. Among the multi-dimensional factors, the neighborhood built environment is crucial for one's health. Although the relationship between the built environment and health in the general population has been thoroughly investigated, it has been ignored in the case of frail older adults, who may have difficulties in their daily basic living skills. A path analysis is constructed to model the proposed theoretical framework involving the neighborhood built environment and health among frail older adults. This study thus aims to investigate the environmental influences on health, and to validate the theoretical framework proposed for health and social services.MethodsThis study used secondary data collected in Hong Kong. A sample of 969 older community dwellers aged 60 or above were frail with at least one activity of daily living. Demographic information, neighborhood built environment data, service utilization, and health conditions were collected from these participants and their caregivers. A path analysis was performed to examine the proposed theoretical framework.ResultsThe health condition was of general concern, including frailty and incapacities in daily activities in frail older adults. Besides psychosocial factors, service use, and caregivers' care quality, the built environment had a significant impact on the health of older adults as well. Specifically, more facilities offering services and groceries, a shorter distance to the nearest metro station, and more greenery exposure are associated with a better-expected health condition among frail older adults.DiscussionThe proposed theoretical framework successfully supplements past negligence on the relationship between the built environment and the health of frail older adults. The findings further imply that policymakers should promote the usability of transit and greenery in neighborhoods and communities. In addition, service utilization should be improved to meet the basic needs of frail older adults in the communities.